The Influence of Socioeconomic Factors in Improving VAT Compliance and Moderated by Tax Knowledge (A Study on MSMEs in Southwest Sumba Regency, East Nusa Tenggara) - Loda, Agustina Koni; Sinarwati, Ni Kadek; Prayudi, Made Aristia (Dinasti International Journal of Economics, Finance & Accounting, 2026)
This study aims to analyze the influence of socio-economic factors on Value Added Tax (VAT) compliance among MSMEs in Southwest Sumba Regency, East Nusa Tenggara Province, Indonesia, with tax knowledge as a moderating variable. The study employs an associative quantitative approach using the Structural Equation Modeling–Partial Least Square (SEM-PLS) method. The sample consists of 307 MSMEs selected through a simple random sampling technique. The results indicate that tax rule complexity, tax sanctions, detection probability, tax ethics, tax fairness, and perceptions of government spending have a positive effect on VAT compliance, while tax service quality does not have a significant effect. The tax knowledge variable only moderates the relationship between tax ethics and VAT compliance in a weakening direction and does not moderate the relationships between the other variables. Overall, VAT compliance is more influenced by structural factors, moral considerations, and perceptions of tax benefits rather than the level of taxpayer knowledge. These findings highlight the importance of strengthening government spending transparency, enforcing tax regulations, and enhancing tax education to improve sustainable MSME compliance.